A Case of Perforation of the Gallbladder in Association with Typhoid Fever - Ponpon Idjradinata; E. Suroto-Hamzah; Sugiri Sugiri (Paediatrica Indonesiana, 1974)
The purpose of this paper is to report a case of rupture of gallbladder in a child in association with typhoid fever.